Congenital adrenal hypoplasia presenting as a chronic respiratory condition. Issue 3 (1st March 2003) - Schwarz, K; Thwaites, R; Minford, A; Day, C; Butler, G
Abstract : We describe two children with oxygen dependence, which resolved when congenital adrenal hypoplasia was diagnosed and treatment initiated. Chronic respiratory distress can be a symptom of adrenal hypoplasia and this should be taken into consideration when investigating a child with unexplained chronic respiratory difficulties. Respiratory symptoms resolve very quickly when the underlying condition is recognised and treated.